Granularidad de datos bajo la perspectiva de información y tecnología: Una interpretación de la Ciencia de la Información - Santos, Plácida L. V. Amorim da Costa [UNESP]; Gonçalves Sant’Ana, Ricardo César [UNESP] (My University, 2013)
The rapid development of technological resources and their use in data access, information use and knowledge generation processes demand from Information Science (IS) a revision and broadening of its referential framework on the possibilities of data and granularity concept interpretation and analysis. The concept of data needs to be scaled, understood and perceived as a basic information flow element, especially at a time when much discussion and legislation is done on content management data access, in favor of its visibility and its use and reuse. The goal is to initiate reflection and debate on the concept of data, data sets and granularity in the field of Information Science. The concepts of data and granularity are presented under the scope of Information and Technology, within Information Science, with a reflection on structured and unstructured data, indicating the relevance of metadata to complement the minimal semantic structure of a given data and in the analysis of its granularity.
Dado e granularidade na perspectiva da informação e tecnologia: Uma interpretação pela ciência da informação
Data granularity under the perspective of information and technology: An interpretation by information science
Keywords: Data; Granularity; Information and technology